The impact of information technology on supply chain management in the Sudanese industrial Case study of Saeed Food Factory (Sebha University Conference Proceedings, 2024)
The study aimed to identify the impact of information technology dimensions (hardware, software, communication networks, and databases) on supply chain management in the Sudanese industrial sector. The study employed a descriptive-analytical methodology and selected a purposive sample of managers and department heads at Saeed Food Factory, totalling 80 individuals. Questionnaires were distributed to the sample members, and 78 were retrieved, yielding a response rate of 97.5%. The questionnaire was used as the primary data collection tool, and multiple regression analysis was employed to test the hypotheses. The results indicated that the level of information technology dimensions is high, suggesting a significant focus on these dimensions within Saeed Food Factory, contributing to overall performance improvement. The respondents' perceptions of supply chain management were also high. There was a statistically significant impact of the combined information technology dimensions on supply chain management. The study recommended that the factory increase its focus on the supply chain, which starts from the supplier to the customer, and educate employees and managers, particularly on transitioning from materials management to supply chain management. Additionally, it emphasized the necessity of leveraging the capabilities provided by information technology in managing the factory's supply chain.